THE STUDY OF MULTISENSORY AS TEACHING PHONICS APPROACH TO IMPROVE THE STUDENTS’ DECODING SKILL - Anastasia Vena Catur Putri; Yohanes Gatot Sutapa Yuliana; Clarry Sada (Universitas Muhammadiyah Makassar, 2025)
The kindergarten students of TK Adicita Mulia require a learning achievement to fulfill their phonics reading skills. However, the students have consistently struggled to recognize the decoding concept as the fundamental learning in reading phonics. Therefore, the study aimed to determine the improvement of students’ decoding phonics using a multisensory teaching approach for kindergarten students of the K1 level at TK Adicita Mulia. The method used in this research is Classroom Action Research (CAR). The multisensory approach involved the students’ auditory, visual, kinesthetic, and tactile senses to understand better decoding concept instruction in recognizing individual sounds and combining them into Consonant, Vowel, Consonant (CVC) words. The improvements focused on the learning outcome of developing decoding skills as the fundamental stage for reading readiness. This research also observed the students’ engagement during the learning process to be attracted to the learning media such as Play-Doh, sand, and flashcards as the interactive learning style for the students. Also, it observed the students’ disruptive behavior, such as uncontrolled behavior, impatience, and lack of focus in the classroom. The results showed that 60% of the students who did not initially improve could demonstrate notable progress in the second cycle. The learning media also generated great enthusiasm during the learning process and positively influenced the change of disruptive behavior into controlled behavior during phonics learning.